Resource Potentials of Spiti : The Cold Mountain Desert of Himachal Pradesh - Kapoor, K S; Bhagat, S (Annals of Arid Zone, 2016)
This paper embodies the socio-economic set up and the related environmental issues in Spiti Valley-the cold mountain desert of Himachal Pradesh. It suggests some ways to carefully utilize this fragile ecosystem and some safeguards against further destruction.